Role of Women in Panchayat Raj in Jhansi District: A Descriptive Study: Socioeconomic Traits and Empowerment of Elected Women in Panchayat Raj Institutions (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study is to identify the socioeconomic traits of elected women inPanchayat Raj institutions. After selecting 224 participants for the study using a proportional stratifiedrandom selection approach, the researcher sought the women's informed permission and conductedinterviews with the elected Village Panchayat officials. The interview was conducted in order to gatherdata using an interviewing approach. Between April and June 2019, information was obtained from them.It is necessary to do a sufficient statistical analysis using SPSS on the data acquired for the study. Bothdescriptive and inferential statistics were employed. Our nation has not kept up with the grassrootsnotion of democracy for women in rural and urban self-governance.